2014
DOI: 10.3389/fpsyg.2014.00605
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability for movement pattern analysis (MPA): measuring patterning of behaviors versus discrete behavior counts as indicators of decision-making style

Abstract: The unique yield of collecting observational data on human movement has received increasing attention in a number of domains, including the study of decision-making style. As such, interest has grown in the nuances of core methodological issues, including the best ways of assessing inter-rater reliability. In this paper we focus on one key topic – the distinction between establishing reliability for the patterning of behaviors as opposed to the computation of raw counts – and suggest that reliability for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Those who relied more upon Perspective as opposed to Assertion reached for more information before arriving at a decision, and had overall longer reaction times. Further work revealed that the type of patterning that is coded in MPA-the individually-referenced balance between Assertion and Perspective-is a superior metric for predicting decision-making process, as compared to raw counts of signature movements representing Assertion and Perspective (Connors et al, 2014). The current work linking MPA to observable decision-making process converges with recent studies, reviewed above, on individual differences in decision making, in two regards.…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…Those who relied more upon Perspective as opposed to Assertion reached for more information before arriving at a decision, and had overall longer reaction times. Further work revealed that the type of patterning that is coded in MPA-the individually-referenced balance between Assertion and Perspective-is a superior metric for predicting decision-making process, as compared to raw counts of signature movements representing Assertion and Perspective (Connors et al, 2014). The current work linking MPA to observable decision-making process converges with recent studies, reviewed above, on individual differences in decision making, in two regards.…”
Section: Introductionsupporting
confidence: 59%
“…Furthermore, recent experimental work has demonstrated that MPA is predictive of decision-making process as elicited in the laboratory (Connors et al, 2013;Connors et al, 2014). A sample of military leaders were shown to vary substantially in the way in which they balanced the need for Assertion and Perspective, based upon their MPA profile.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations